A "hands-on" approach to teaching and learning of electronic communications subject - Rosemizi, Abd Rahim; Mohd Fisol, Osman; Junita, Mohd Nordin; Shariffah Zarihan, Syed Zaharim Helmi (Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 2009)
Electronic Communications is one of the core subject for the degree course in Communications Engineering. The understanding of electronic section in a communications system is the key element of the subject. Due to the fact that this subject is actually a mixture of both electronics and communications systems, the learning process of it might get complicated and confusing. This paper outlines the successful practical oriented approach to teaching and learning of the subject including the objectives, subject structure, outcomes, and skills trained during practical sessions.